2019
DOI: 10.1002/prep.201900285
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of New Azido Esters Derived from Malonic Acid

Abstract: Three new α,α-diazidated azido esters derived from malonic acid were synthesized and characterized with a method of diazidation under mild reaction conditions. They are energy-rich, small, liquid molecules which contain up to six azido moieties. The three synthesized compounds were compared to already known azidated malonic acid esters regarding their density, thermal stability, calculated heat of formation and energetic properties. Further they were tested and classified for their sensitivities according to U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Organic azides have been well investigated during the past decades, as they are widely used in various different fields of application ranging from pharmaceutical and medical science [1,2] over precursors for click chemistry [3] to chemical biology [4] and the agricultural sector. [5] The azido moiety is also commonly found in the area of energetic materials, [6] with many materials like plasticizers, hypergolic ionic liquids and binders containing at least one functional azido group. [7,8] Figure 1 shows a selection of commonly used organic azides in exemplary fields of application, as well as an example for the importance of geminal diazides in cyclisation reactions towards tetrazoles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic azides have been well investigated during the past decades, as they are widely used in various different fields of application ranging from pharmaceutical and medical science [1,2] over precursors for click chemistry [3] to chemical biology [4] and the agricultural sector. [5] The azido moiety is also commonly found in the area of energetic materials, [6] with many materials like plasticizers, hypergolic ionic liquids and binders containing at least one functional azido group. [7,8] Figure 1 shows a selection of commonly used organic azides in exemplary fields of application, as well as an example for the importance of geminal diazides in cyclisation reactions towards tetrazoles.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 9. Molecular unit of guanidinium 2,2-diazidoacetate(6). Thermal ellipsoids of non-hydrogen atoms are drawn at the 50 % probability level and hydrogen atoms are shown as small spheres of arbitrary radius.…”
mentioning
confidence: 99%
“…The five most common explosives tested, and the number of observations per explosive, are given in Table . Unless otherwise noted, we use log E 50 to represent sensitivity, where “log” is the base-10 logarithm, as in Kamlet, Nefati et al, and Wang et al The main source of data was legacy LANL tests; however, many of the data were obtained from the published scientific literature. , …”
Section: Datamentioning
confidence: 99%
“…Addition of the fuel component increases the performance of the propellant blend by reducing the high adiabatic temperature of the ionic liquid binary aqueous solution and further stabilizing the combustion process. Typically, methanol is used to control the burning rate of the monopropellant while the ammonium nitrate (AN) is used as a stabilizer [10] beside other stabilizing additives; a new article by M. Claßen et al [11] introduced novel additive promoters of new azido esters and suggested it would improve the total energy and performance of ionic liquid propellants. As an example, the maximum specific impulse of 78 wt% ADN in water mixture (Ionic Liquid) is 192 s when used as monopropellant, while the specific impulse rises to 252 s when methanol (molecular fuel) is added to the mixture, as in the case of LMP-103S (63.4 wt% ADN, 25.4 wt% water and 11.2 wt% methanol) at a nozzle area expansion ratio of 50 [12] as cited in [3].…”
Section: Energetic Ionic Liquids (Eils)mentioning
confidence: 99%